Nephroprotective activity of Annona Squamosa leaves against paracetamol-induced nephrotoxicity in rats: in vitro and in vivo experiments - S. Neelima; P. Dwarakanadha Reddy; Chandra Sekhar Kothapalli Bannoth (SpringerOpen, 2020)
Abstract Background Paracetamol (PCM), being extensively adapted analgesic and anti-inflammatory drug all over the world, beyond therapeutic dosages, the oxidative stress-involved nephrotoxicity has been evidenced. However, herbal plants are the windfall for the humankind providing solution for most of the wellness breakdowns. Annona squamosa (AS) is one of such plants with enormous therapeutic and nutraceutical potencies. The main aspiration of the current investigation is to evaluate the nephroprotective ability of ethanolic extract of Annona squamosa (EEAS) leaves against paracetamol-induced nephrotoxicity using in vitro human embryonic kidney (HEK)-293 cells and in vivo experiments in Wistar rats through biochemical parameters, oxidative parameters, and histopathological findings. Results When HEK-293 cells were incubated with PCM, an increased cell death associated with alterations in the morphology of normal cells was observed. At variable concentrations, HEK-293 cells co-treated with PCM and EEAS extracts gave a significant improvement in cell growth on comparing with PCM treatment showing cytoprotective feature of EEAS with an IC50 28.75 μg/mL. In vivo nephroprotective property was assessed from the amount of blood urea nitrogen (BUN) along with creatinine and uric acid which were reduced (P < 0.001) within serum and compact levels of glutathione, catalase, and superoxide dismutase which were termed as GSH, CAT, and SOD, respectively, were increased (P < 0.001) in kidney tissue homogenate in the treated groups than the PCM alone group. Results were additionally supported by histopathological observations. Conclusion The results exhibited that EEAS has impending benefits against PCM-induced nephrotoxicity through in vitro and in vivo experiments.